2009
DOI: 10.2478/v10019-009-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia-anorexia syndrome and skeletal muscle wasting

Abstract: Background. Cachexia-anorexia syndrome is a common and important indicator of cancer. It occurs in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
1
4
0
1
Order By: Relevance
“…In addition, it has been widely demonstrated that resistance training enhances the rate of mixed muscle protein synthesis in older participants guarantying an effective muscle proteins turnover and reducing muscle wasting (55,56,57). Moreover, several studies agree with the idea that physical activity can exerts important functions against many other age-related markers improving the general adaptive response of specific anti-oxidant and stress proteins (58).…”
Section: Exercise As a Tool To Counteract Sarcopenia And Cancer-relatsupporting
confidence: 50%
“…In addition, it has been widely demonstrated that resistance training enhances the rate of mixed muscle protein synthesis in older participants guarantying an effective muscle proteins turnover and reducing muscle wasting (55,56,57). Moreover, several studies agree with the idea that physical activity can exerts important functions against many other age-related markers improving the general adaptive response of specific anti-oxidant and stress proteins (58).…”
Section: Exercise As a Tool To Counteract Sarcopenia And Cancer-relatsupporting
confidence: 50%
“…We decided to check BMI regularly in OSCC patients because of the known fact that cachexia-anorexia syndrome occurs in 30 to 80% of cancer patients. 72 Although BMI did not reach the malnutrition level it still points to the need of an even better nutritional support of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The strong relationship between the hypothalamus and total energy balance of the organism both in the physiological and pathological situations, in particular in relation to body weight, includes also a neuroregulatory component. [15][16][17][18] 3.…”
Section: Pathogenesis Of Tumour Cachexiamentioning
confidence: 99%